2018
DOI: 10.5005/jp-journals-10015-1580
|View full text |Cite
|
Sign up to set email alerts
|

Composite Diametral Tensile Strength

Abstract: Aim:The aim of this study was to evaluate and compare the diametral tensile strength (DTS) of 4 types of composite materials including bulk fill type (tetric evo ceram) cured with two different curing intensities. Materials and methods:Four types of light-activated composite materials of A3 shade were selected for this study: Tetric Evo Ceram-Ivoclar Vivadent; Ceram X.mono-Dentsply; Nano Ceram-Bright-DMP; Estelite Sigma Quick-Tokuyama. Twenty specimens of each composite material were prepared: ten specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Estelite Σ Quick has slightly lower DTS than Tetric EvoCeram Bleach. Similarly, in a previous study, the mean DTS of Estelite Σ Quick was found to be 35.95 (±1.070) MPa with a 650 mW/cm 2 lamp; 44.81 (±1.2) MPa with a 1200 mW/cm 2 lamp; 38.15 (±2.1) MPa for Tetric EvoCeram Bulkfill with a 650 mW/cm 2 lamp; and 48.8 (±1.8) MPa with a 1200 mW/cm 2 lamp [35]. These results are higher than those in the present study, probably due to the shorter irradiation time (8 s per side).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Estelite Σ Quick has slightly lower DTS than Tetric EvoCeram Bleach. Similarly, in a previous study, the mean DTS of Estelite Σ Quick was found to be 35.95 (±1.070) MPa with a 650 mW/cm 2 lamp; 44.81 (±1.2) MPa with a 1200 mW/cm 2 lamp; 38.15 (±2.1) MPa for Tetric EvoCeram Bulkfill with a 650 mW/cm 2 lamp; and 48.8 (±1.8) MPa with a 1200 mW/cm 2 lamp [35]. These results are higher than those in the present study, probably due to the shorter irradiation time (8 s per side).…”
Section: Discussionmentioning
confidence: 93%
“…Materials with high contraction stress during polymerization may be particularly prone to deterioration of the bond strength with dentine, resulting in microleakage and secondary caries [38]. Shrinkage stress can rapidly build up during polymerization by replacing the van der Waals spaces by covalent bonds, thus reducing the free volume [35,36]. Shrinkage values are dependent on material composition, cavity configuration and compliance and the viscoelastic nature of material [38,39].…”
Section: Discussionmentioning
confidence: 99%